Karakteristik Gaya Belajar: (Studi Empiris Pada Mahasiswa Pendidikan Teknologi Informasi Iib Darmajaya) - Khodijah, Siti; Situmorang, Klaudia SB; Nuryana, Sapta Adi; Hasibuan, Muhammad Said (Journal of Digital Literacy and Volunteering, 2025)
This study aims to describe the characteristics of students towards aspects of 4 different learning styles, Perceptions of VARK, Felder Silverman, Kolbs and Honey and Mumford learning styles. The population in this study were students of the Information Technology Education Study Program at the Darmajaya Institute of Informatics and Business with a total of 25 students, This study had 15 participants with a percentage of Men (46.6%) and Women (53.4%), in addition there were 10 students who did not participate in this study. Data were collected through questionnaires which were then analyzed using descriptive statistics. The results of the study showed differences in each individual who has a variety of learning styles, for that understanding a learning style can make it easier for students to implement learning strategies that are of interest according to their wishes so that Information Technology Education students can increase creativity and effectiveness to improve learning achievement.